MATHEMATICAL MODEL OF PRESSURE CHANGE IN AUTOMOBILE PNEUMATICAL TIRE DEPENDING ON OPERATING TEMPERATURE (Academic journal Industrial Machine Building Civil Engineering, 2019)
It has been established that in the process of operation pressure ratings in the tires of many cars differs from those recommended by the production plant. Is leads to performance degradation of tires traveling properties and their loss of life.The pressure excursion from the normative value may be caused either by an error during tire inflation, or by the fact that thedifference between the operating temperature and the temperature of the inflating air has not considered. Using athematicalstatistical methods of data processing, there has been deduced the mathematical relationship between pressure in the pneumatical tire at the operating temperature and the required pressure of inflating air into the tire, if the temperatures of inflationand operation differ.
Keywords: pneumatical tire; inflation pressure; three-level plan; planning matrix; mathematical model